Answer:
nope
Step-by-step explanation:
Apply dot product which must = 0 for orthogonality.
In this case,
-(3)(2) + (-2)(-2) + (-3)(1) + (1)(4) = -1.
Answer:
area of a 1st
Step-by-step explanation:
Um... I think you meant <span>24:96 = 5:x
In that case, x=20
</span>
Answer:
(52 - 4) * (13 - 7)
Step-by-step explanation:
<u>Step 1: Convert words into an expression</u>
52 minus 4 times the difference of 13 and 7.
(52 - 4) * (13 - 7)
Answer: (52 - 4) * (13 - 7)
If needed simplify
(52 - 4) * (13 - 7)
48 * 6
288